Behavioral Financial Factors and Bank Managers Financial Performance: Evidence from Semarang - Abdul Syukur; Awanis Linati Haziroh; Maria Safitri (Fakultas Ekonomi dan Bisnis Universitas Dian Nuswantoro, 2026)
This study aims to examine the effects of financial self-efficacy, financial literacy, and financial decision-making on the financial performance of bank managers in Semarang City. A quantitative approach was employed with 125 respondents selected through purposive sampling from both state-owned and private banks. Data were collected using a 1–7 Likert scale questionnaire and analyzed using PLS-SEM with SmartPLS 4. The results indicate that financial decision-making and financial self-efficacy have positive and significant effects on financial performance, while financial literacy has no significant effect. These findings highlight the importance of behavioral factors and decision-making quality in improving the financial performance of bank managers..